2004
DOI: 10.1063/1.1649459
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic annealing in III-nitrides under ion bombardment

Abstract: Articles you may be interested inEffect of the growth temperature and the AlN mole fraction on In incorporation and properties of quaternary IIInitride layers grown by molecular beam epitaxy J. Appl. Phys.We study the evolution of structural defects in Al x Ga 1Ϫx N films ͑with xϭ0.0-0.6) bombarded with kilo-electron-volt heavy ions at 77 and 300 K. We use a combination of Rutherford backscattering/ channeling spectrometry and cross-sectional transmission electron microscopy. Results show that an increase in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 44 publications
7
46
1
Order By: Relevance
“…In our He + irradiated sample the electron concentration saturates at about 18 19 . However, Kucheyev states that the two most likely mechanisms are an increase in electrostatic energy associated with substitutional disorder and electrostatically lowering energy barriers for defect interaction processes as ionicity increases 20 . What is known is that very ionic materials, such as ZnO, exhibit strong dynamic annealing, and ZnO and CdO have comparable ionicity 21 .…”
Section: Resultsmentioning
confidence: 99%
“…In our He + irradiated sample the electron concentration saturates at about 18 19 . However, Kucheyev states that the two most likely mechanisms are an increase in electrostatic energy associated with substitutional disorder and electrostatically lowering energy barriers for defect interaction processes as ionicity increases 20 . What is known is that very ionic materials, such as ZnO, exhibit strong dynamic annealing, and ZnO and CdO have comparable ionicity 21 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, the minimum hydrogen dose required to observe surface blistering in Si, Ge or SiC is about 3 × 10 16 H + 2 cm −2 [11,13,14]. It is known from the literature that the group III nitrides such as AlN and GaN exhibit very efficient dynamic annealing of the implantation-induced defects [20][21][22][23][24]. In the process of blistering, the implanted hydrogen interacts with the implantation-induced damage inside the semiconductor lattice that ultimately leads to the formation of extended defects such as nanovoids/nanoplatelets [9,10,13,25].…”
Section: Resultsmentioning
confidence: 99%
“…In their work on InGaN alloys, Kucheyev et al [33] pointed out the detrimental effect of indium on the structure stability, and they showed that an increase of the In content degrades the dynamic annealing efficiency during the ion implantation. eV/atom, respectively: these values correspond to experimental data reported in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The high resistance to amorphization of GaN and AlN has been ascribed to an efficient dynamic annealing during implantation [32,33] which enables the defect annihilation and the arrangement into an array of planar defects. In absence of dynamic annealing, the damage accumulation leads to a complete lattice disordering or to amorphization when each atom has been moved approximately one time (1 displacement per atom (dpa)).…”
Section: Discussionmentioning
confidence: 99%